The study of the source material of potatoes under conditions of Kirov region - N. F. Sintsova; I. V. Lyskova (Аграрная наука Евро-Северо-Востока, 2020)
The article presents the results of study of potato varieties and hybrids collection in the conditions of Kirov region, including varieties of modern Russian and foreign collections, interspecific hybrids of VIR, Falenskaya selection station and other scientific institutions for 300-350 samples annually. The study was conducted in contrasting weather conditions in 2017-2019. Sources of high productivity (705…887 g/bush): 129-10, Effekt (Russia), Lukawa (Czechoslovakia), Zorachka, Uladar (Belarus), Colomba (Netherlands) and others, and large potato tuber (100…140 g): Bellarosa (Germany), Lilea (Belarus), Irbitsky, Krepysh (Russia) were revealed. Due to big epiphytotic of late blight in 2017 varieties with high field resistance of foliage to late blight were revealed (7-9 points): Kufri Anara (India), Suzorye, Ragneda, Alpinist (Belarus), Gubernator, Skazka, Effekt, Vdohnovenie, Fritella, Legenda, 90-5-30, 55-03 (Russia); 387110.4, 678019 (Peru) and others. In 2019 samples with high late blight resistance of tubers were selected (9 points): Lilea (Belarus), Udacha, Ognivo, Lubava Legenda, 122-29, 90-6-2, 194-00, 591-97, 55-03, 56-09, 172-11, 6-1, 39-10, 132-07 (Russia), 389746.2, 678019 (BL-22), 678009 (BL-1.10) (Peru). Varieties of field resistance to viral diseases were selected: Lukawa (Czechoslovakia), Yanka, Ragneda, Zorachka, Charaunik (Belarus), Franzi, Albina, Kolomba, Sofia (Germany), Lazar, Skazka, Mayak, Udacha, Krasavchik, Charodey), Zolsky, Matushka, Nayada, Sudarynya, Kolobok, 42-7-40, 112-04, 184-05, 28-06, 48-224-10, 455-08, 431-08, 142-09, 5-7К, 1-13К, 218-12, 286-08, 40-14К, 16-25-1К, 16-29-33К, 56-09, 289-13. Assessment of starch content allowed to select varieties and hybrids with starch content above 20%: Bashkirsky, Zolsky, Lazar (Russia), Uladar, Vektar Belorussky, Manifest, Zhuravinka, Zdabytok (Belarus) and others. Hybrids 268-09 and 289-13 combined high starch content and high late blight resistance. The most valuable source material for potato breeding in the Kirov region are varieties and hybrids with a complex manifestation of warnings: Bellarosa, Albina, Sofia (Germany), 129-09, 40-14, 7-2В, 5-7 К, 268-08, 141-14, 289-13, 455-08, 56-09, 149-14, Kamensky, Irbitsky, Debryansk, Effekt (Russia), Kolamba (Netherlands), Zorachka, Сharaunik, Uladar, Altair, Lilea (Belarus), Lukawa (Czechoslovakia).